2010
DOI: 10.1007/s10742-010-0062-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rurality on mental and physical health

Abstract: The effects of rurality on physical and mental health are examined in analyses of a national dataset, the Community Tracking Survey, 2000-2001, that includes individual level observations from household interviews. We merge it with county level data reflecting community resources and use econometric methods to analyze this multi-level data. The statistical analysis of the impact of the choice of definition on outcomes and on the estimates and significance of explanatory variables in the model is presented usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…On the other hand, using the same analysis from Stern et al (2010) for MCS-12, the standard deviation of …xed e¤ects for the same 60 sites is 0:64 which is quite small relative to the standard deviation of MCS-12 in the NSADMHP reported in Table 5A. Thus, the signi…cance of missing geography-speci…c …xed e¤ects varies over di¤erent measures of mental health.…”
Section: Community Fixed E¤ectsmentioning
confidence: 81%
See 3 more Smart Citations
“…On the other hand, using the same analysis from Stern et al (2010) for MCS-12, the standard deviation of …xed e¤ects for the same 60 sites is 0:64 which is quite small relative to the standard deviation of MCS-12 in the NSADMHP reported in Table 5A. Thus, the signi…cance of missing geography-speci…c …xed e¤ects varies over di¤erent measures of mental health.…”
Section: Community Fixed E¤ectsmentioning
confidence: 81%
“…It has a moderately sized list of demographic, economic, health insurance, physical health, mental health, and health care utilization questions. Among other models, Stern et al (2010) estimate a correlated probit model for depression, 27 allowing for a wide set of personal characteristics, community characteristics, 28 interactions between community and personal characteristics, and site dummy variables. The community dummy variables control for community e¤ects not captured by the observed community characteristics included directly in the model.…”
Section: Community Tracking Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…Measuring rural health disparities is challenging due to the lack of a singular definition of "rural" in the disparities literature, none of which may be adequate to capture known drivers of rural health disparities (Coburn et al, 2007). Accordingly, research has shown that application of different definitions may produce different results (Meilleur et al, 2013;Stern et al, 2010). Several classification codes are available only at a county level, limiting the ability of researchers to understand the impact of more granular variations in factors that drive disparities such as distance to care, or landscape-related hazardous roads which can vary widely in large area rural counties (DeGuzman, Cohn, et al, 2017;Pesut et al, 2010).…”
mentioning
confidence: 99%